Jaundice and Associated Factors among Hospitalized Neonates in Tripoli-Libya - Rehab Walli; Abed Alnaser Drbal; Jannat Albashir (AlQalam Journal of Medical and Applied Sciences, 2024)
Jaundice can occur in full term and preterm neonates within the first week of life. Severe neonatal jaundice can lead to death. This study was conducted to address the common risk factors associating with jaundice among newborns admitted to the intensive care unit at Aljala Hospital at Tripoli city in Libya. The study is performed in the period from June to November in the year 2023. A total of randomly selected 72 neonates paired with their mothers were involved. Data were collected from the medical files. In this study we found that 57% of the neonates were males and 43% were females. Also, neonatal jaundice was more prevalent among full term (75%) than preterm (25%) hospitalized newborns. We found that 43% of our neonates were hospitalized due to neonatal jaundice only, while 33% of the neonates were hospitalized due to neonatal jaundice and Rh-negative mother. In about 30% of the neonates in this study, sepsis and respiratory distress were common neonatal illness coexisting with neonatal jaundice. Additionally, neonates with positive Rh (83%) and blood group O have a higher level of total serum bilirubin than those with negative Rh of other blood groups. We found that the prevalence of neonatal jaundice is higher in full term male neonates than females. The commonest cases are neonates with Rh+ blood groups, specifically O+. Sepsis and respiratory distress are markedly associated with neonatal jaundice in this study. يمكن أن يحدث اليرقان عند الأطفال حديثي الولادة في فترة الحمل الكاملة والخدج خلال الأسبوع الأول من الحياة. ويمكن أن يؤدي اليرقان الوليدي الشديد إلى الوفاة. أجريت هذه الدراسة لمعالجة عوامل الخطر الشائعة المرتبطة باليرقان بين الأطفال حديثي الولادة الذين تم إدخالهم إلى وحدة العناية المركزة في مستشفى الجلاء في مدينة طرابلس في ليبيا. أجريت الدراسة في الفترة من يونيو إلى نوفمبر في عام 2023. شارك في الدراسة 72 طفلًا حديثي الولادة تم اختيارهم عشوائيًا مع أمهاتهم. تم جمع البيانات من الملفات الطبية. في هذه الدراسة وجدنا أن 57٪ من الأطفال حديثي الولادة كانوا من الذكور و 43٪ من الإناث. كما كان اليرقان الوليدي أكثر انتشارًا بين الأطفال حديثي الولادة في فترة الحمل الكاملة (75٪) مقارنة بالأطفال الخدج (25٪) في المستشفى. وجدنا أن 43% من الأطفال حديثي الولادة دخلوا المستشفى بسبب اليرقان الوليدي فقط، بينما دخل 33% من الأطفال حديثي الولادة المستشفى بسبب اليرقان الوليدي والأمهات ذات العامل الرايزيسي السلبي. وفي حوالي 30% من الأطفال حديثي الولادة في هذه الدراسة، كان الإنتان وضيق التنفس من الأمراض الوليدية الشائعة التي تصاحب اليرقان الوليدي. بالإضافة إلى ذلك، فإن الأطفال حديثي الولادة ذوي العامل الرايزيسي الإيجابي (83%) وفصيلة الدم O لديهم مستوى أعلى من البيليروبين الكلي في المصل مقارنة بأولئك ذوي العامل الرايزيسي السلبي من فصائل الدم الأخرى. وجدنا أن انتشار اليرقان الوليدي أعلى في الأطفال حديثي الولادة الذكور من الإناث. الحالات الأكثر شيوعًا هي الأطفال حديثي الولادة ذوي فصائل الدم Rh+، وخاصة O+. يرتبط الإنتان وضيق التنفس بشكل ملحوظ باليرقان الوليدي في هذه الدراسة